AN ANALYSIS OF RACISM IN ANGIE THOMAS NOVEL CONCRETE ROSE: Discrimination, Prejudice, Racism - Novita Nuriyah Hasyim; Danu Wahyono (Fakultas Sastra Universitas Gresik, 2021)
This Study is entitled An Analysis Racism in Angie Thomas Novel Concrete Rose. It aims to describe the forms of racism reflected in the novel and to describe Maverick struggle to fight against Racism. The study is designed as descriptive qualitative study since the object of the study and the result of analysis are presented in descriptive form. The approach used is sociological approach The sociological approach to literary works is one type of approach in the sociology of literature that is used to analyze the events, characterizations, and settings contained in the short stories that are read. Humans take actions intentionally to accomplish their goals, at the same time, human actions have unintended consequences (unintentional consequences) of setting that impact on subsequent human actions. Humans according to this theory are agents of purposeful actors who have reasons for their activities and are able to describe those reasons repeatedly. This study describes the main character who is trying to achieve his goals by dealing with racial conflicts that occur in his environment The author concludes that there are 2 types of racism in the novel Concrete Rose. The first is Prejudice. Prejudice is a prejudice or negative assessment of an object without knowing the truth first. Angie Thomas shows indirectly how prejudice occurs. Maverick's bad prejudice occurs because he is a black person. In America they have a bad reputation. The second is discrimination. Discrimination is an act that treats a person or group differently and unfairly on the basis of the characteristics of that person or group. Discrimination by police and paramedics against the main character is very, very detrimental and has a negative impact on the main character.